Ticagrelor Versus Aspirin in Acute Embolic Stroke of Undetermined Source. Issue 9 (September 2017) - Amarenco, Pierre; Albers, Gregory W.; Denison, Hans; Easton, J. Donald; Evans, Scott R.; Held, Peter; Hill, Michael D.; Jonasson, Jenny; Kasner, Scott E.; Ladenvall, Per; Minematsu, Kazuo; Molina, Carlos A.; et al.
Abstract : Background and Purpose—: Ticagrelor is an effective antiplatelet therapy among patients with atherosclerotic disease and, therefore, could be more effective than aspirin in preventing recurrent stroke and cardiovascular events among patients with embolic stroke of unknown source (ESUS), which includes patients with ipsilateral stenosis <50% and aortic arch atherosclerosis. Methods—: We randomized 13 199 patients with a noncardioembolic, nonsevere ischemic stroke or high-risk transient ischemic attack to ticagrelor (180 mg loading dose on day 1 followed by 90 mg twice daily for days 2–90) or aspirin (300 mg on day 1 followed by 100 mg daily for days 2–90) within 24 hours of symptom onset. In all patients, investigators informed on the presence of ipsilateral stenosis ≥50%, small deep infarct <15 mm, and on cardiac source of embolism detected after enrollment or rare causes, which allowed to construct an ESUS category in all other patients with documented brain infarction. The primary end point was the time to the occurrence of stroke, myocardial infarction, or death within 90 days. Results—: ESUS was identified in 4329 (32.8%) patients. There was no treatment-by-ESUS category interaction ( P =0.83). Hazard ratio in ESUS patients was 0.87 (95% confidence interval, 0.68–1.10; P =0.24). However, hazard ratio was 0.51 (95% confidence interval, 0.29–0.90; P =0.02) in ESUS patients with ipsilateral stenosis <50% or aortic arch atherosclerosis (n=961) and 0.98 (95% confidence interval, 0.76–1.27; P =0.89) in the remaining ESUS patients (n=3368; P for heterogeneity =0.04). Conclusions—: In this post hoc, exploratory analysis, we found no treatment-by-ESUS category interaction. ESUS subgroups have heterogeneous response to treatment (Funded by AstraZeneca). Clinical Trial Registration—: URL:http://www.c linicaltrials.gov . Unique identifier: NCT01994720. Abstract : Supplemental Digital Content is available in the text.